Repellency Assays with Plant Extracts and Essential Oils from Schinus molle var. areira (L) (Anacardiaceae) and DEET against Nezara viridula L. (Hemiptera: Pentatomidae) - González, Jorge Werdin; Gutiérrez, Maria Mercedes; Ferrero, Adriana Alicia (BioAssay, 2012)
Nezara viridula L. is one of the key pests in soybean crops. The aim of this work was to study the repellent effects of ethanolic and hexanic extracts, essential oils from leaves and fruits of Schinus molle var. areira and N, N-diethyl-m-toluamide (DEET) against adults of N. viridula in a choice-test arena. Half of a circular white filter paper of 9 cm. diameter was treated with extracts, essential oils or DEET and the other half with solvent alone. Each extract was tested at 1.572 µg/cm2, 3.144 µg/cm2 and 6.288 µg/cm2, each essential oil and DEET were tested at 78.6 µg/cm2, 157.2 µg/cm2 and 314.4 µg/cm2. Repellency asssays were carried out at 1 and 24 h. Ethanolic extracts from leaves and fruits were neutral at 1 and 24 h. Fruits and leaves hexanic extracts showed repellent activity at 1 h; however, hexanic extracts from leaves at the lowest dose lost the effect at 24 h. Essential oils from leaves (157.2 µg/cm2 and 314.4 µg/cm2) showed repellent effect at 1 h and the essential oils from fruits at these same doses maintained the activity for 24 h. DEET was repellent at all doses evaluated.